Impact of meniscal coverage on subchondral bone mineral density of the proximal tibia in female subjects – A cross-sectional in vivo study using QCT - Sannmann, Frederike; Laredo, Jean-Denis; Chappard, Christine; Engelke, Klaus (Bone (New York, N.Y.), 2020)
To verify earlier data in cadavers that in female subjects with OA meniscal coverage is associated with lowered bone mineral density of the underlying subchondral bone in the proximal tibia by investigating the local bone mineral density (BMD) distribution within the epiphysis. BMD of the subchondral bone of the tibia was measured by QCT in 67 elderly females diagnosed with OA (Kellgren-Lawrence grades 2–3). The epiphysis was subdivided along the axis of the tibia into a subchondral-epiphyseal VOI covering the first 5-6 mm below the subchondral bone plate, a mid-epiphyseal VOI covering the adjacent 7–8 and a juxtaphyseal VOI of another 7-8 mm that bordered the growth plate. These VIOs were further divided into lateral and medial and then into anterior, mid and posterior sub-VOIs. Finally, all subVOIs were divided in one subVOI covered by the menisci (CM) and another not covered by the menisci (nCM). BMD ratios of these two subVOIs were compared. In the subchondral epiphysis BMD was significantly lower (Medial: mean BMDdiff = 125 mg/cm3, p<0.001; Lateral: mean BMDdiff = 56 mg/cm3p < 0.001) in subVOIs covered by the meniscus compared to subVOIs not covered by the meniscus. The BMD difference was no longer significant in the mid epiphysis (Medial: mean BMDdiff = 10 mg/cm3, p>0.82; Lateral: mean BMDdiff = 7 mg/cm3, p=0.99) and was reversed in the juxtaphysis. With a few exceptions these BMD differences were independent of the lateral-medial and the anterior-mid-posterior position. BMD significantly (p<0.05) decreased with age independent on whether the location was covered or uncovered by the meniscus, however the BMD ratio of the corresponding nCM and CM subVOIs did not significantly (p>0.1) change with age. In-vivo QCT measurements of the BMD distribution in the proximal tibia indicate a protective effect of the menisci in the subchondral bone close to the joint. This protective effect is age independent despite the overall age-related decrease of BMD. •Menisci retain protective effect on bone mineral density in osteoarthritic knees.•Tibial subchondral bone density is lower under menisci than not under menisci.•Medial subchondral tibia shows significantly larger differences than lateral tibia.•Protective effect decreases distal of the joint, but is independent of age.